Understanding the Nature and Extent of Pharmaceutical Industry Payments to Nonphysician Clinicians - Karanges, Emily A. (JAMA Intern Med, 2019)
This case study analysis assesses the nature and extent of pharmaceutical industry payments to nonphysician clinicians in Australia and investigates the possible reasons for sponsorship.